Multicenter evaluation of mechanical thrombectomy for distal medium vessel occlusions with National Institute of Health Stroke Scale scores ≥ 6 and ≤ 6 - Kühn, Anna Luisa; Möhlenbruch, Markus Alfred; Jesser, Jessica; Weyland, Charlotte S. (Journal of neurology, 2024)
While mechanical thrombectomy is considered standard of care for large vessel occlusions, scientific evidence to support treatment for distal and medium vessel occlusions remains scarce. - Purpose: To evaluate feasibility, safety, and outcomes in patients with low National Institute of Health Stroke Scale scores undergoing mechanical thrombectomy for treatment of distal medium vessel occlusions. - Materials and methods: Retrospective data review and analysis of prospectively maintained databases at 41 academic centers in North America, Asia, and Europe between January 2017 and January 2022. Characteristics and outcomes were compared between groups with low stroke scale score (≤ 6) versus and higher stroke scale scores (> 6). Propensity score matching using the optimal pair matching method and 1:1 ratio was performed. - Results: Data were collected on a total of 1068 patients. After propensity score matching, there were a total of 676 patients included in the final analysis, with 338 patients in each group. High successful reperfusion rates were seen in both groups, 90.2% in ≤ 6 and 88.7% in the > 6 stroke scale groups. The frequency of excellent and good functional outcome was seen more common in low versus higher stroke scale score patients (64.5% and 81.1% versus 39.3% and 58.6%, respectively). The 90-day mortality rate observed in the ≤ 6 stroke scale group was 5.3% versus 13.3% in the > 6 stroke scale group. - Conclusion: Mechanical thrombectomy in distal and medium vessel occlusions, specifically in patients with low stroke scale scores is feasible, though it may not necessarily improve outcomes over IVT.
Autoren: Anna Luisa Kühn, Markus A. Möhlenbruch, Jessica Jesser, Charlotte Weyland [und 87 weitere] im Namen des MAD‑MT Consortiums
Online veröffentlicht: 5. Juli 2024
Gesehen am 17.03.2025